Economic Analysis of the Consequences of Government Intervention in Maize Market in Iraq by using (PAM) Policy Analysis Matrix (Producer Sample in the year 2011) - Kameis, Wigdan; Hayef, Alkareem; Raheem, Abdul jaleel; Al–Khafaji, Jasim (Journal of Kerbala for Agricultural Sciences, 2014)
This research care for determining the effects of government intervention in maize market for producers sample in the year 2011 by using Policy analysis matrix (PAM) approach .This usage will help us to determine protection coefficients and comparative advantage coefficients, in order to know the effect of government intervention in Maize price. The value of nominal protection coefficient (NPC) and effective protection coefficient (EPC) were (1.5) and (2.2) indicates that there was a positive subsidy given to producers. The profitability coefficient value for Maize was (4.74) indicated that government encourage efficient technology and the producers make high profit in that year . The value of domestic resource cost was (0.031) positive and less than one that means there was comparative advantage in Maize production for producers in the sample. And so the value of Producer Subsidy Ratio was (52.2 %) that mean there was a high subsidy from government to them. The value of Private Cost Coefficient Ratio was less than one about (0.306) that mean investment in Maize production more than cost so the investors had profit in that year.